Identification and provenance determination of stone tesserae used in mosaics from Roman Celeia, Slovenia. (4th January 2022) - Miletić, Snježana; Šmuc, Andrej; Dolenec, Matej; Miler, Miloš; Mladenovič, Ajda; Gutman Levstik, Maja; Dolenec, Sabina
Abstract: This study examined the provenance of stone tesserae from three Roman mosaics from Celje, Slovenia, using optical microscopy, X‐ray fluorescence spectroscopy, scanning electron microscopy, and X‐ray diffraction. Nine microfacies were distinguished. Miliolid limestones identified in the white tesserae, and mudstones/laminated wackestones in the black tesserae, suggest they originated from the Karst region. The sparry limestone in the yellow tesserae probably originates from the Mediterranean. The mudstone/wackestone with planktonic foraminifera in the red tesserae originates from an outcrop in southwestern Slovenia. Green tesserae tuffs are of local origin, whereas the white tuffs could originate from Italian Oligo‐Miocene volcanism rhyolites.